Mycorrhizae and Rhizobacteria on Precambrian Rocky Gold Mine Tailings: II. Mine-Adapted Symbionts Alleviate Soil Element Imbalance for a Better Nutritional Status of White Spruce Seedlings - Nadeau, Martin B.; Laur, Joan; Khasa, Damase P. (Frontiers in Plant Science, 2018)
In the context of a phytorestoration project, the purpose of this study was to assess the respective contribution to the nutritional status of Picea glauca seedlings of ectomycorrhizae and rhizobacteria native or not to the Sigma-Lamaque gold mine wastes in northern Quebec, Canada. In a glasshouse experiment, inoculated plants were grown for 32 weeks on coarse waste rocks or fine tailings obtained from the mining site. The survival, health, growth, and nutritional status of plants were better on coarse waste rocks than on fine tailings. Fe and Ca were especially found at high levels in plant tissues but at much lower concentrations on waste rocks. Interestingly, inoculation of microsymbionts had only minimal effects on N, P, K, and Mg plant status that were indeed close or within the concentration range encountered in healthy seedlings. However, both fungal and bacterial treatments improved Fe and Ca concentrations in plant tissues. Fe concentration in the foliage of plants inoculated with the fungi Tricholoma scalpturatum Tri. scalp. MBN0213 GenBank #KC840613 and Cadophora finlandia Cad. fin. MBN0213 GenBank #KC840625 was reduced by >50%. Both fungi were isolated from the mining site. The rhizobacteria, Azotobacter chroococcum, also improved plant Fe level in some cases. Regarding Ca nutritional status, the native bacterial strain Pseudomonas putida MBN0213 GenBank #AY391278 was the only symbiont that reduced foliar content by up to 23%. Ca concentration was negatively correlated with the fungal mycorrhization rate of seedling roots. This relation was especially strong (r = -0.66, p-value ≤ 0.0001) in the case of C. finlandia. Also, a similar relationship existed with root Fe concentration (r = -0.44, p-value ≤ 0.0001). In fact, results showed that seedling performance was more correlated with elevated Ca and Fe concentration in planta than with nutrient deficiency. Also, native microsymbionts were capable of regulating seedling nutrition in the poor substrate of the Sigma-Lamaque gold mine tailings.